Reproductive Performance and Physiological Responses in Awassi Ewes Under Intravaginal Sponges Application and Fed Selenium and Vitamin E - Saeed, O. A.; Ahmed, N. K.; Taha, M. M.; Abedal-Majed, M. A.; Ali, F. M.; Samsudin, A. A. (Faculty of Animal Science, IPB University, 2024)
This study was carried out to investigate the impact of feeding selenium (Se) and vitamin E on the physiological and reproductive performance of 18 multiparous Awassi ewes through the breeding season. The ewes received three levels of oral selenium-vitamin E for 60 days until the study was completed. The experimental ewes were assigned into three groups; the control group (SE0) received 2 mL of sterile saline per head, the second group (SE1) received 1.5 mL/head Se and vitamin E (150 mg α-Tocopherol acetate + 0.15 mg Sodium selenite), while the third group (SE2) received 3 mL/head (150 mg α-Tocopherol acetate + 0.15 mg Sodium selenite). The SE1 and SE2 groups demonstrated significant highest (p<0.05) rate of conception and overall pregnancy. The study results showed the lambing rate in the SE2 group increased significantly (p<0.05) compared to the other groups. All groups had low plasma progesterone levels on day 14, even though concentrations increased in SE0 and SE1, which had higher progesterone levels than SE2. SE1 had the highest estrogen concentration on day 16 compared to SE0 and SE2. On day 14, the SE0 group had a significantly lower ALT enzyme compared to the SE1 and SE2 groups. SE1 had significantly lower mean corpuscular volume (MCV), white blood cells (WBC), and platelets (PLT) concentrations than the other two groups. Overall, the estrus synchronization program and the administration of Se and vitamin E resulted in a significant improvement in pregnancy and lambing rates among Awassi ewes. Physiological and reproductive potential of sheep can be increased by improving their diet throughout the period of reproduction by including Se and vitamin E.